Ki-67 and MCM-2 in Dental Follicle and Odontogenic Cysts: The Effects of Inflammation on Proliferative Markers - Nurhan Güler; Nil Çomunoğlu; Fatih Cabbar (The Scientific World Journal)
The aim of this study was to investigate whether there is any association between inflammation and the expression of markers of cell cycle entry (Ki-67 and MCM-2) in dental follicle (DF) of asymptomatic impacted teeth and odontogenic cysts. The study consisted of 70 DFs and 20 odontogenic cysts (radicular cyst (RC), dentigerous cyst (DC) and keratocytic odontogenic tumor (KCOT) located at posterior mandibular region. Histological findings of inflammation for all specimen and mucous cell prosoplasia, squamous metaplasia, glandular epithelium for all DFs were stained with hematoxyline and eosin, periodic acid schiff, alcian blue, and mucin. Epithelial cell proliferation was determined by using immunohistochemical labeling for Ki-67 and MCM-2. The histologic examinations showed 16% mucous cell prosoplasia, 54% squamous metaplasia, 20% glandular epithelium, 37% inflammation. Inflammation was detected in all RCs and %62 in DF, %43 in DC and KCOT. Positive correlation was found between the inflammation of DF and odontogenic cysts (P<0.01). The mean Ki-67 and MCM-2 expressions were found 9,64±5,99 and 6,34±3,81 in DF, 11,85±9,01 and 13,6±9,94 in odontogenic cysts, respectively. While the mean Ki-67 expressions were statistically significant in DF and KCOT (P<0.01), MCM-2 were significant in RC and KCOT (P<0.01). MCM-2 expresion in RCs were statistically significant than KCOT (P<0.01). The results of this study indicated that the higher MCM-2 expressions in RC than the KCOT might be related to the inflammation and this protein might be more sensitive to inflammation.